2012
DOI: 10.1515/hf-2011-0260
|View full text |Cite
|
Sign up to set email alerts
|

Sorption isotherms of thermally modified wood

Abstract: The hygroscopic properties of thermally modified wood have been studied in terms of adsorption and desorption processes. Poplar ( Populus spp.) and European beech ( Fagus sylvatica L.) were in focus. The obtained isotherms were parameterized with the models of HailwoodHorrobin, Guggenheim-Anderson-deBoer, generalized D ' Arcy and Watt, and Yanniotis and Blahovec. The changes in equilibrium moisture content (EMC) were quantified, and the accessibility of water vapor to the sorption sites was determined. The mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
1
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(39 citation statements)
references
References 30 publications
5
22
1
7
Order By: Relevance
“…MC difference between the absorption and desorption isotherms, but this result appears to be correlated with the general reduction in MC at given RH. A similar general reduction in MC is found for thermal modification of wood; however, this treatment appears to increase the absolute sorption hysteresis (Olek et al 2013). Automated sorption balances are useful for studies of sorption hysteresis, and several published studies have focused on this phenomenon.…”
Section: Automated Sorption Balancessupporting
confidence: 54%
“…MC difference between the absorption and desorption isotherms, but this result appears to be correlated with the general reduction in MC at given RH. A similar general reduction in MC is found for thermal modification of wood; however, this treatment appears to increase the absolute sorption hysteresis (Olek et al 2013). Automated sorption balances are useful for studies of sorption hysteresis, and several published studies have focused on this phenomenon.…”
Section: Automated Sorption Balancessupporting
confidence: 54%
“…Thermal modification reduced the equilibrium moisture content by about 50% for the highest temperature (240 °C) and the longest treatment time (5 h). This observation is consistent with the earlier findings of Metsä-Kortelainen et al (2006) and Olek et al (2013).…”
Section: Resultssupporting
confidence: 94%
“…Hill (2006) stated that hysteresis is reduced after thermal treatment, whereas Militz (2002) found no effect. Olek et al (2013) clearly demonstrated that the hysteresis coefficient increased with the modification temperature.…”
Section: Introductionmentioning
confidence: 89%
“…More recently, TMT is also considered for indoor use, for instance, as parquet flooring or furniture (Militz 2008;Jones 2012). Higher durability as well as dimensional stability of TMT is closely related to lower water sorption (Tjeerdsma et al 1998;Welzbacher 2007;Olek et al 2013;Ringman et al 2013). In other words, the hygroscopicity of wood is reduced through thermal modification due to changes of chemical composition and structural changes of the cell wall.…”
Section: Introductionmentioning
confidence: 99%